The Effect Of Water On The Mechanical Properties And Microstructures Of Granitic Rocks At High Pressures And High Temperatures - Ove Alm (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Wet and dry specimens of three rocks of approximately granitic composition were deformed at different experimental conditions. These experiments were carried out in order to study the extent to which water, either added or released from mineral reactions, may affect the mechanical properties and the microstructure of these rocks. The experiments were conducted in a Griggs' hot creep apparatus at temperatures and pressures up to 900ºC and 1000 MPa respectively; and most of them were performed in the constant strain rate mode [(1.10-6 < t < 1 • 10-4 s-1 )]. All three rocks were low porosity rocks, and the wet specimens never contained more than 0.9 wt % of added water. The experimental results are, however, quite unequivocal: They show that wet rocks are weaker than dry ones. A significant difference is even found for rocks tested in uniaxial compression at room temperature. A few experiments carried out on specimens obtained from larger prestressed rock cores indicated that the central parts of these cores were more likely to contain more microcracks than the ends. Optical microscope examinations revealed that extensive microcracking takes place even at the highest temperatures, where other mechanisms such as slip and dislocation creep also become important. Very little partial melting could be observed except for the specimens deformed at 900ºC.